Suicidality and Psychosis Following Vaping Related Lung Injury - Lin, Samuel K; Percifield, Chad; Hommer, Zach; Demijohn, Brad; Janney, Carol A. (Archives of Clinical and Medical Case Reports, 2022)
Background: Vaping-related lung injuries are of great concern, particularly among those who vape tetrahydrocannabinol (THC). Research also indicates that THC use increases the risk of developing psychotic disorders, particularly with use of high potency THC. Case Presentation: The case of a 20-year-old female with a history of depression and daily vaping of THC is presented. She was medically hospitalized and treated for a vaping-related lung injury, followed by a psychiatric hospitalization for treatment of depression and suicidal ideation. The patient endorsed new-onset psychotic symptoms which required targeted treatment. A second psychiatric hospitalization ensued after an intervening suicide attempt. Conclusions: Vaping of THC poses clear risks to the physical health of its users, including vaping-related lung injury. Although the patient presented in this case recovered from her lung injury, her subsequent need for psychiatric treatment also highlights the detrimental effects from vaping THC on mental health, ranging from depression to psychotic symptoms and even to suicidality.